2017
DOI: 10.1016/j.msea.2017.08.119
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen diffusion and trapping in a low copper 7xxx aluminium alloy investigated by Scanning Kelvin Probe Force Microscopy

Abstract: A B S T R A C TThe susceptibility to hydrogen embrittlement (HE) of the 7046 aluminium alloy (AA 7046) was investigated. Samples of AA 7046 corresponding to different ageing temperature/time couples were hydrogenated by cathodic charging in a H 2 SO 4 solution. Scanning Kelvin Probe Force Microscopy (SKPFM) combined with global hydrogen amount measurements allowed apparent hydrogen diffusion coefficients (D app ) to be measured: the decrease of the D app values with the increase of the ageing duration was attr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 30 publications
6
17
1
Order By: Relevance
“…Mechanical tests performed on H-free and H charged tensile samples showed that hydrogen in grain boundaries induced intergranular rupture and hydrogen trapped at carbides and matrix/precipitates interfaces induced cleavage [2]. The fracture surface of the outgassed sample has shown only cleavage that reinforced the fact that hydrogen content after desorption treatment was mainly related to hydrogen trapped at matrix/precipitates interfaces and thus responsible for a large part for the OCP value ac cording to the work of Oger et al (33]. These results have shown that hydrogen was able to modify the electrochemical behavior of alloy 718 in relation with diffusible and trapped hydrogen content.…”
Section: Effect Of Hydrogen On Electrochemical Behaviorsupporting
confidence: 65%
See 1 more Smart Citation
“…Mechanical tests performed on H-free and H charged tensile samples showed that hydrogen in grain boundaries induced intergranular rupture and hydrogen trapped at carbides and matrix/precipitates interfaces induced cleavage [2]. The fracture surface of the outgassed sample has shown only cleavage that reinforced the fact that hydrogen content after desorption treatment was mainly related to hydrogen trapped at matrix/precipitates interfaces and thus responsible for a large part for the OCP value ac cording to the work of Oger et al (33]. These results have shown that hydrogen was able to modify the electrochemical behavior of alloy 718 in relation with diffusible and trapped hydrogen content.…”
Section: Effect Of Hydrogen On Electrochemical Behaviorsupporting
confidence: 65%
“…Indeed, the precipitates which act as trapping sites distort the lattice and/or create interfaces at which the hydrogen atoms will distort the lattice less. In this sense, the influence of hydrogen on OCP should give indica tion about the interaction between hydrogen and precipitates/ matrix interfaces in subsurface as recently shown by Oger et al [33]. Further, analysis of the OCP curves requires to consider H desorption during OCP measurements at 25 °C, as shown in Fig.…”
Section: Effect Of Hydrogen On Electrochemical Behaviormentioning
confidence: 88%
“…This fits well with our observations. In recent years, the hydrogen distribution within Cu-free Al-Zn-Mg alloys has been studied and it has been suggested that the bulk precipitates are important in hydrogen trapping [41][42][43]. Motionless dislocations have also been demonstrated as important hydrogen trapping sites [44].…”
Section: Discussionmentioning
confidence: 99%
“…These local defects can then evolve into cracks according to different types of damage mechanisms such as preferential dissolution of the grain boundaries for alloys susceptible to intergranular corrosion, stress concentration at the crack tip, with mechanisms assisted or not by hydrogen [1][2][3]. Concerning the 7xxx series aluminium alloys, many studies highlighted the effect of hydrogen during SCC mechanisms [4][5][6][7][8]. Classically, SCC behaviour of aluminium alloys is studied by slow strain rate tests (SSRT) in aqueous environment in order to exacerbate the role of the corrosive environment as well as the adsorption and the diffusivity/transport of the absorbed species [9][10][11].…”
Section: Introductionmentioning
confidence: 99%